Simultaneous cardiac and respiratory frequency measurement based on a single fiber Bragg grating sensor - Silva, A. F. (2011)
A respiratory and cardiac-frequency sensor has been designed and manufactured to monitor both components with a single fiber Bragg grating (FBG) sensor. The main innovation of the explored system is the structure in which the FBG sensor is embedded. A specially developed polymeric foil allowed the simultaneous detection of heart rate and respiration cycles. The PVC has been designed to enhance the sensor sensitivity. In order to retrieve both components individually, a signal processing system was implemented for filtering out the respiratory and cardiac frequencies. The developed solution was tested along with a commercial device for referencing, from which the proposed system reliability is concluded. This optical-fiber system type has found an application niche in magnetic resonance imaging (MRI) exam rooms, where no other types of sensors than optical ones are advised to enter due to the electromagnetic interference.